Evaluating user satisfaction of Universiti Tun Hussein Onn Malaysia Total Campus Integrated System (TCIS) / Mohd Hatta Mohamed Ali @ Md Hani - Mohamed Ali @ Md Hani, Mohd Hatta (2012)
e- Services is becomes a required system in organisations nowadays. This e-Service system can help the organisation to deliver their services in a better way. Hence, Universiti Tun Hussein Onn Malaysia (UTHM) is applying the Total Campus Integrated System (TCIS) as their e-Service application. With the objective to penetrate quality of service in the administrative services in the university. However, whether this implementation and the transformation that have been made cater the user satisfaction? Does it give an impact to the service quality? This issued is related with the customer satisfaction and this study is to evaluate the user satisfaction and perception towards the TCIS. User satisfaction is believed to have an impact in term of service quality. Therefore the effort on better understanding the co- related between service quality and user satisfaction must be done. Preliminary research has shown that TCIS is not yet being evaluated. With the 11 critical success factor and 7 demographic profile, adopted from user satisfaction model by (Bailey and Pearson, 1983; Doll and Torkzadeh, 1988; Yoo and Donthu, 2001; Yang, et al., 2005), Sugianto and Tojib, (2006) Wixom and Todd (2005) and Ong et al. (2009), a model of user satisfaction evaluation assessment for TCIS has been introduced. 400 staff was randomly selected to participate in the research. The results were revised and revalidate to understand the user satisfaction. Recommendations were provided after the level of satisfaction has been identified. It is believed by the recommendation that will be provide it will help the development team to understand about the staff perception, trend and behaviour. Furthermore, this will also help to improve the quality of the system and enhance the University Tun Hussein Onn Malaysia in developing best practice of e-Service portal and enhancing the user satisfactions.